A review of recent studies on the enrichment of eggs and poultry meat with omega-3 polyunsaturated fatty acids: novel findings and unanswered questions - Robert G. Elkin; Kevin J. Harvatine (Poultry Science, 2023)
ABSTRACT: Studies from our laboratory over the past decade have yielded new information with regard to the dietary enrichment of eggs and poultry meat with omega-3 (n-3) polyunsaturated fatty acids (PUFA) but have also generated a number of unanswered questions. In this review, we summarize the novel findings from this work, identify knowledge gaps, and offer possible explanations for some perplexing observations. Specifically discussed are: 1) Why feeding laying hens and broilers an oil rich in stearidonic acid (SDA; 18:4 n-3), which theoretically bypasses the putative rate-limiting step in the hepatic n-3 PUFA biosynthetic pathway, does not enrich egg yolks and tissues with very long-chain (VLC; ≥20 C) n-3 PUFA to the same degree as obtained by feeding birds oils rich in preformed VLC n-3 PUFA; 2) Why in hens fed an SDA-rich oil, SDA fails to accumulate in egg yolk but is readily incorporated into adipose tissue; 3) How oils rich in oleic acid (OA; 18:1 n-9), when co-fed with various sources of n-3 PUFA, attenuates egg and tissue n-3 PUFA contents or rescues egg production when co-fed with a level of docosahexaenoic acid (DHA; 22:6 n-3) that causes severe hypotriglyceridemia; and 4) Why the efficiency of VLC n-3 PUFA deposition into eggs and poultry meat is inversely related to the dietary content of α-linolenic acid (ALA; 18:3 n-3), SDA, or DHA.